(untitled) (Journal of The Colloquium for Information Systems Security Education, 2014)
This qualitative case study examined the difference in management and technical personnel’s perceptions of the effectiveness of DoD 8570 mandated Information Assurance (IA) certification training at a Department of Defense facility located on the west coast of the United States. The results indicated participants found DoD 8570 IA certification training to be of limited utility. Generally, participants recognized a need for personnel new to the IA workforce to learn baseline IA concepts, but felt the mandate did little to build an essential body of IA experts within the Department of Defense. The study revealed opportunities for the Department of Defense to adopt improved training practices that are more in line with organizational and stakeholder needs and thus more effective at creating an expert IA workforce. The current research provides impetus for future research relevant to the participating facility, the Department of Defense as a whole, and any organization looking to strengthen its IA workforce.